Improving Social Rehabilitation Services For Physical Disabilities Through Technology and Family Involvement At East Java Provincial Social Service - Drajat Suhartono; Albab Albab; Priyanto Priyanto; Brotati Chakraborty (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
This study investigates strategies for improving social rehabilitation services for people with physical disabilities through technology-based approaches and family involvement at UPT Social Rehabilitation Bina Laras Pasuruan, East Java. Employing a qualitative case study design, data were collected through in-depth interviews, focus group discussions, observation, and documentation with rehabilitation staff, persons with disabilities, family members, and technology specialists. Findings reveal that integrating digital technologies—including mobile health applications, telemedicine platforms, and assistive devices—significantly enhances service accessibility and monitoring capabilities. Structured family involvement programs, encompassing psychoeducation sessions, home-based care training, and support groups, demonstrate substantial improvements in rehabilitation outcomes. Critical success factors include adequate technological infrastructure, staff digital literacy, family commitment, and inter-agency coordination. Challenges include the digital divide, resistance to technological adoption, and sustainability concerns. The research concludes that a hybrid model combining technology-enabled services with intensive family participation offers the most promising approach and recommends policy frameworks that institutionalise these innovations while ensuring equitable access across diverse beneficiary populations